Interelectronic-interaction effects on the two-photon decay rates of heavy He-like ions - Volotka, Andrey V.; Surzhykov, Andrey; Shabaev, V. M.; Plunien, G. (Physical review. A, Atomic, molecular, and optical physics, 2011)
Based on a rigorous quantum electrodynamics (QED) approach, a theoretical analysis is performed for the two-photon transitions in heavy He-like ions. Special attention is paid to the interelectronic-interaction corrections to the decay rates that are taken into account within the two-time Green-function method. Detailed calculations are carried out for the two-photon transitions 21S0→11S0 and 23S1→11S0 in He-like ions within the range of nuclear numbers Z=28-92. The total decay rates together with the spectral distributions are given. The obtained results are compared with experimental values and previous calculations.
Gesehen am 27.10.2022